Clinical characteristics and treatment of Spontaneous Coronary Artery Dissection in Young Women Undergoing Percutaneous Coronary Intervention. Issue 1 (January 2021) - Inoue, Yosuke; Tanaka, Akihito; Asano, Hiroshi; Uemura, Yusuke; Takagi, Kensuke; Ohashi, Taiki; Tanaka, Miho; Umemoto, Norio; Ajioka, Masayoshi; Tashiro, Hiroshi; Watarai, Masato; Morishima, Itsuro; et al.
Abstract : Background: Spontaneous coronary artery dissection (SCAD) has recently been recognized as a cause of acute coronary syndrome (ACS), especially in young women. However, the characteristics, optimal treatment, and prognosis of patients who experience SCAD have not been fully described. Methods: Data were retrospectively collected from a multicenter registry. Among 187 young women less than 60 years of age who underwent percutaneous coronary intervention, 19 (10.2%) with SCAD were identified through coronary angiography. Clinical characteristics and outcomes were investigated. Results: Those with SCAD less frequently exhibited coronary risk factors, such as diabetes, dyslipidemia, and smoking, than those without SCAD. Intense emotional and/or physical stress was more frequently observed as a prominent precipitating factor in cases of SCAD. All 19 SCAD patients presented with ACS, 7 of whom were treated using stents, and the other 12 treated without stents. During a median follow-up of 960 days (interquartile range, 686–1504 days), two recurrent coronary artery dissections occurred within 7 days, both of which occurred in a vessel other than that in which primary dissection occurred. There were no deaths or recurrent dissection after 1 week. Conclusion: SCAD was not uncommon among young Japanese women requiring percutaneous coronary intervention. Patients with SCAD exhibited fewer coronary risk factors and more precipitating factors than those without SCAD, and long-term clinical outcomes after an early period appeared to be favorable.